2003
DOI: 10.1210/jc.2002-021160
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-Rich Lipoproteins Are Associated with Hypertension in Preeclampsia

Abstract: Disorders of the lipoprotein metabolism are a major cause of endothelial dysfunction that may result in hypertension and proteinuria, clinical hallmarks of preeclampsia (PE). Lipoproteins and low-density lipoprotein (LDL) subfractions were investigated in 15 women with severe PE and compared with 23 women with a normal course of pregnancy. Compared with normal pregnancy, in PE apolipoprotein (apo)B in very low-density lipoprotein was increased by 76% (P = 0.008), and the triglyceride content of intermediate de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 31 publications
9
64
3
Order By: Relevance
“…This study was compatible with other studies that there were major disturbances in lipid profile in preeclamptic & eclamptic patient as compared with normal pregnancy [9][10][11][12][13] . However, there were variations in level of significance of various lipid indices alterations, for example, this study clearly showed significant increase in total serum cholesterol in our preeclamptic & eclamptic cases, this is consistant with Adegoke 14 , but inconsistent with Jayanta De 15 , this bias may be related to the number of patients in other study.…”
Section: Statisticssupporting
confidence: 92%
“…This study was compatible with other studies that there were major disturbances in lipid profile in preeclamptic & eclamptic patient as compared with normal pregnancy [9][10][11][12][13] . However, there were variations in level of significance of various lipid indices alterations, for example, this study clearly showed significant increase in total serum cholesterol in our preeclamptic & eclamptic cases, this is consistant with Adegoke 14 , but inconsistent with Jayanta De 15 , this bias may be related to the number of patients in other study.…”
Section: Statisticssupporting
confidence: 92%
“…PE is associated with placental dysfunction, oxidative stress [1,89], dyslipidaemia [16,90] and endothelial cell activation, and is a major cause of maternal and fetal morbidity and mortality [88] A proatherogenic lipid profile, characterized by increased TG levels with reduced HDL concentration [90,91] and increased small, dense LDL particles [90] has been described. In contrast other studies demonstrated a dominance of buoyant LDL-1 and a significant decreased of small, dense LDL, namely LDL-5 and LDL-6 [92]. Notwithstanding, it has been suggested that an abnormal lipid metabolism may not only be a manifestation of PE, but dyslipidaemia may play an essential role in its pathogenesis Apart from genetic predisposition, the second group of disorders associated with an increased risk of PE includes a variety of chronic conditions such as dyslipidaemia, diabetes mellitus, hypertension, renal diseases, and various thrombophilias [93].…”
Section: Fetal Lipoproteins In Pre-eclampsiacontrasting
confidence: 61%
“…Various studies claim that abnormal lipid synthesis leading to increase of thromboxane level and the decrease of prostaglandin levels as well as the imbalance of lipid peroxidase and antioxidants is responsible for preeclampsia Table-2 [5][6][7]. The characteristic preeclampsia uteroplacental lesion is similar to atherosclerotic lesions; both display vessel wall necrosis and accumulation of lipid laden foam cells, a hallmark of oxidized low-density lipoproteins (LDL) [8].…”
Section: Introductionmentioning
confidence: 99%